Important role of pedestal ion temperature in the ELM mitigation by supersonic molecular beam injection. (8th September 2016) - Ma, Q.; Yu, D.L.; Chen, C.Y.; Wei, Y.L.; Zhong, W.L.; Zou, X.L.; Zuo, H.Y.; Du, J.L.; Liu, L.; Dong, C.F.; Shi, Z.B.; Zhao, K.J.; et al.
Abstract: Edge localized mode (ELM) is successfully mitigated by helium and deuterium supersonic molecular beam injections (SMBIs) on HL-2A. During the ELM mitigation by SMBIs, gradients of ion temperature ( T i ) and electron density are softened in the pedestal. It has been observed that the averaged gradient of the T i decreases around 44% and the well depth of radial electric field ( E r ) is reduced by the SMBI during ELM mitigation. Furthermore, at least 20% decrements of T i have to be attained to achieve a noticeable increase (decrease) of the ELM frequency (amplitude). In addition, the duration of ELM mitigation with helium SMBI is much longer than that with deuterium, likely due to the higher level of recycling neutral gas compared to that of deuterium; in the case of ELM mitigation by helium SMBI, the recovery duration of the density gradient is much shorter (10–20 ms) than that of T i (up to 40 ms or longer), indicating the importance of the T i in the ELM mitigation by SMBI. Finally, it has been observed that the T i is reduced before the beginning of the ELM mitigation, suggesting that the mechanism of the ELM mitigation by SMBI is closely related to the cooling effect.